2014
DOI: 10.1007/s00280-014-2564-z
|View full text |Cite
|
Sign up to set email alerts
|

Importance of branched-chain amino acids in patients with liver cirrhosis and advanced hepatocellular carcinoma receiving hepatic arterial infusion chemotherapy

Abstract: Branched-chain amino acids might improve the survival and C-P score by increasing serum albumin in C-P B patients with aHCC receiving HAIC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 32 publications
0
14
1
Order By: Relevance
“…The administration of branched-chain amino acid effectively maintains the Child-Pugh score during chemotherapy of patients with advanced HCC [20,21]. In contrast, the present study did not detect a significant effect of consumption of branched-chain amino acids on maintaining Child-Pugh scores.…”
Section: Discussioncontrasting
confidence: 53%
“…The administration of branched-chain amino acid effectively maintains the Child-Pugh score during chemotherapy of patients with advanced HCC [20,21]. In contrast, the present study did not detect a significant effect of consumption of branched-chain amino acids on maintaining Child-Pugh scores.…”
Section: Discussioncontrasting
confidence: 53%
“…Eventually, 11 eligible articles relating to a total of 974 subjects (450 in BCAA groups and 524 in control groups) were chosen for this meta-analysis. Of the 11 eligible studies, six were RCTs [1924] and five were cohorts (of which three were retrospective and two prospective designs) [2528, 32]. Out of the six RCTs, four received a Jadad score of 4 or 5 and were considered high-quality, while the other two were deemed low quality because of scores lower than 4 (Additional file 1: Table.…”
Section: Resultsmentioning
confidence: 99%
“…Information about 1-year mortality was reported in nine studies [19, 20, 22, 2428, 32] while 3-year mortality was reported in five studies [19, 22, 24, 25, 27]. A fixed-effect model was used to analyze mortality at the two time-points since there was no significant heterogeneity among these studies (P = 0.912, I 2  = 0.0 %; P = 0.129, I 2  = 43.9 %, respectively).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The important regulatory role of BCAAs (Leu, Ile, and Val) as nutrient signals promoting protein synthesis [1] and as donors of nitrogen to Ala and Gln synthesis in skeletal muscle and other tissues [2,3] have led to their use in treating medical conditions, and as nutritional supplements [4,5]. Abnormal BCAA concentrations, on the other hand, have been linked to metabolic, cardiovascular, and neurological disorders [6,7].…”
Section: Introductionmentioning
confidence: 99%